ANALYSIS OF READING COMPREHENSION FINAL TEST AT ENGLISH DEPARTMENT OF MUHAMMADIYAH ACEH UNIVERSITY - Rahmatun Nisa; Cut Mawar Helmanda (Getsempena English Education Journal, 2020)
The aim of this study is not only to analyze the model and the items test set by lecturer of Reading Comprehension subject but also the ability of students according to the item questions of each final test. This study analyzes the contents taken from the document test and it used descriptive quantitative approach. The gained data derived from three Reading subjects, they are: Intensive Reading Comprehension, Reading Comprehension III dan Academic Reading. The total number of the items from those three subjects is 60 items. The findings revealed that the kind of questions asked by lecturers varied, namely; Multiple Choice, Open-ended Question, Word Matching, and True and False. Based on the those documents the writer found that 6 questions about Main Idea, 16 questions about Vocabulary, 4 about references, 6 questions about inference and 28 questions about details. Then, the results of students' reading ability in answering the items were; main idea: ​​63.59%, Detail: 76, 92%, Inference: 44,04, Reference ; 86, 89% and Vocabulary : 73,45 %. From the five aspects students were better to answer questions in the Reference item. The implication of this research is to provide input to examiners and lecturers in giving material and in testing students at the end of the semester and to improve the ability to make test items.